Demistifikasie van die metafoor "die kerk as bruid" - Botha, Annelie (HTS teologiese studies, 2007)
Demystification of the methaphor “the church as bride” Because of the important role language, imagery and metaphors plays in the lives of human beings, it is necessary to explore the origins and implications of metaphors that could be potentially harmful to the quality of women’s lives. The metaphor that is the focus of this article, is that of “the church as bride”. This metaphor is an example of how metaphors and language have an impact on women’s self-understanding and subject quality of their lives. It is an example of how patriarchal structures, culture and language affect the lives of women. In a follow-up article the way in which this metaphor is used in the marriage formulary of the Nederduitsch Hervormde Church of Africa is investigated. This formulary is specifically based on Ephesians 5:21-33 in which the metaphor of “the church as bride” is found.